Study on Mechanical Properties of Silica Fume-Bitumen Emulsion Stabilized Peat - Mohd Akram, Muhammad Nur Iman (Universiti Teknologi PETRONAS, 2021)
The stabilization of peat is an essential technique to enhance the mechanical properties of the most problematic soil (peat), making is suitable to withstand heaving loading. In this project, the effectiveness of using optimized silica fume-bitumen emulsion to strengthen and stabilized the peat soil were assessed. The objectives of the study are to investigate the indexed properties of Teluk Intan peat, the California bearing ratio (CBR), and unconfined compressive strength (UCS) of stabilized and unstabilized peat. For optimization of silica fume in bitumen emulsion based on the settlement, storage stability, viscosity and sieve test using RSM software. Then, all of the components were compared to percentage of binder content and mixing speed. With the optimized 4.324% of silica fume in bitumen emulsion, UCS and CBR tests are conducted with different percentage of optimized silica fume-bitumen emulsion which are 5%, 8% and 10% in peat. For UCS test, the curing period for all samples are 24 hours.